The transcription factor Ndt80 is a repressor of Candida parapsilosis virulence attributes. Issue 1 (31st December 2021) - Branco, Joana; Martins-Cruz, Cláudia; Rodrigues, Lisa; Silva, Raquel M.; Araújo-Gomes, Nuno; Gonçalves, Teresa; Miranda, Isabel M.; Rodrigues, Acácio G.
ABSTRACT: Candida parapsilosis is an emergent opportunistic yeast among hospital settings that affects mainly neonates and immunocompromised patients. Its most remarkable virulence traits are the ability to adhere to prosthetic materials, as well as the formation of biofilm on abiotic surfaces. The Ndt80 transcription factor was identified as one of the regulators of biofilm formation by C. parapsilosis ; however, its function in this process was not yet clarified. By knocking out NDT80 ( CPAR2-213640 ) gene, or even just one single copy of the gene, we observed substantial alterations of virulence attributes, including morphogenetic changes, adhesion and biofilm growth profiles. Both ndt80Δ and ndt80ΔΔ mutants changed colony and cell morphologies from smooth, yeast-shaped to crepe and pseudohyphal elongated forms, exhibiting promoted adherence to polystyrene microspheres and notably, forming a higher amount of biofilm compared to wild-type strain. Interestingly, we identified transcription factors Ume6, Cph2, Cwh41, Ace2, Bcr1, protein kinase Mkc1 and adhesin Als7 to be under Ndt80 negative regulation, partially explaining the phenotypes displayed by the ndt80ΔΔ mutant. Furthermore, ndt80ΔΔ pseudohyphae adhered more rapidly and were more resistant to murine macrophage attack, becoming deleterious to such cells after phagocytosis. Unexpectedly, our findings provide the first evidence for a direct role of Ndt80 as a repressor of C. parapsilosis virulence attributes. This finding shows that C. parapsilosis Ndt80 functionally diverges from its homolog in the close related fungal pathogen C. albicans .